Challenges in the diagnostics of mantle cell lymphoma in an elderly comorbid patient - Rostislav V. Binyakovskiy; Svetlana V. Borisovskaya; Oleg D. Zaharov; Dmitry G. Kiselev; Sergey V. Lepkov; Alexander V. Melekhov; Igor G. Nikitin; Alexander V. Salikov (Alʹmanah Kliničeskoj Mediciny)
We present a case of a rare lymphoproliferative disease diagnosed while differentiating between the causes of exudative-constrictive pericarditis.